2015
DOI: 10.1017/s1355617715000028
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Metabolic Syndrome on Language Functions in Aging

Abstract: This study explored effects of the metabolic syndrome (MetS) on language in aging. MetS is a constellation of five vascular and metabolic risk factors associated with the development of chronic diseases and increased risk of mortality, as well as brain and cognitive impairments. We tested 281 English-speaking older adults aged 55-84, free of stroke and dementia. Presence of MetS was based on the harmonized criteria (Alberti et al., 2009). Language performance was assessed by measures of accuracy and reaction t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 47 publications
(71 reference statements)
2
11
0
1
Order By: Relevance
“…The results are also in line with reports that education is related to naming performance [ 9 ], and that individuals with higher education decline less steeply than are individuals with lower education on at least some cognitive tasks [ 12 ]. Moreover, our results replicate previous findings that demonstrated associations between health status and naming scores [ 10 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results are also in line with reports that education is related to naming performance [ 9 ], and that individuals with higher education decline less steeply than are individuals with lower education on at least some cognitive tasks [ 12 ]. Moreover, our results replicate previous findings that demonstrated associations between health status and naming scores [ 10 ].…”
Section: Discussionsupporting
confidence: 91%
“…While self-rated health is a good predictor of mortality [ 17 ], it could be too general to incur a differential effect on each of the naming tasks studied here. Although changes in naming in healthy older adults might be related to risk factors for brain damage [ 9 , 10 ], there is no reason to assume that these risk factors lead to specific lesions that cause difficulties in one type of stimuli but not the other.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As we adjusted for 3 of 4 components of the metabolic syndrome (all except dyslipidemia), it follows that obesity might be one driving force behind the cognitive impairment seen in people with the metabolic syndrome. 8 13 Mediation of the obesity-cognition association by presence of diabetes or hypertension is unlikely, as controlling for mediating factors would have led to a profound reduction in effect size. However, the possibility of an influence of subclinical insulin resistance or subclinical elevated blood pressure remains.…”
Section: Discussionmentioning
confidence: 99%
“… 6 It has been estimated that 22% of people aged over 70 years in the USA are currently cognitively impaired, 7 and epidemiological studies have frequently demonstrated associations with the metabolic syndrome. 8 13 Diabetes, hypertension and obesity together contribute to the diagnostic criteria of the metabolic syndrome 14 and have each been assessed in detail for their relationship with cognitive outcome. Links of diabetes to presence and risk of future cognitive impairment are well established, 15 , 16 while the evidence is less clear for obesity and hypertension.…”
Section: Introductionmentioning
confidence: 99%